Metode pembelajaran menarik untuk siswa jenjang Sekolah Dasar (SD) - Firmansyah, Akhmad (Maliki Interdisciplinary Journal, 2024)
Elementary school is the first step in learning about self-character, with that the need for learning methods as supporters and assistant in learning activities Quality education is influenced by effecient and effective learning methods. The purpose of this study was to analyze learning methods in elementary school and the factors that cause laziness in students in these schools and how to prevent them The location chosen was SD Negeri 4 Bakam. The research method uses a qualitative and deskriptive methods. The results of study prove that quality education depends on learning methods in addition, learning methods are also one of the factors that cause the lazineess in students. With that a learning can be categories as effective if students are able to quickly understand the material with this learning method.